A SIGNIFICANT ASSESSMENT OF NANO-FERTILIZERS AND IT’S IMPORTANCE - Pooja Srishti, V. Sankara Vel, Sajith. S, R. Lakshmi, Summera Rafiq, SK. Jasmine Shahina (Chelonian Research Foundation, 2024)
One of the challenges faced by the agriculture sector is ensuring that plants have sufficient bioavailability of minerals. Therefore, it is crucial to have mechanisms in place that allow for the controlled release of nutrients during planting, as well as innovative procedures that avoid any negative consequences. The application of nanotechnology in agriculture offers numerous advantages, including enhanced nutrient utilization by plants and waste reduction. Nano-fertilizers are a burgeoning technology and a continuously growing category of agrochemicals, offering potential solutions to the advancement of sustainable agriculture. The objective of this study is to provide an updated and comprehensive analysis of several aspects related to nanomaterials. These include different methods of synthesizing nano-fertilizers, potential mechanisms by which plants absorb these materials, and the benefits and drawbacks associated with their use. Additionally, this paper provides a comprehensive review of the primary literature in the field, focusing on recent investigations that employ the principles of green chemistry. Keywords: Sustainable agriculture, Agrochemicals, Emerging technologies, Nano-fertilizers, Green chemistry.